Artificial iris implantation in various iris defects and lens conditions - Mayer, Christian; Tandogan, Tamer; Hoffmann, Andrea E.; Khoramnia, Ramin (Journal of cataract and refractive surgery, 2017)
We describe 6 surgical techniques used to implant a silicone iris prosthesis: sector-shaped iris segments that require suturing, injector-assisted sulcus fixation, injector-assisted capsular bag fixation with an intraocular lens (IOL) and capsular tension ring, folded iris tissue implanted with a forceps and sutured to the sclera with a scleral-fixated IOL, “sandwich” or “backpack” implantation with an IOL, and open-sky implantation with a perforating keratoplasty. The results of the techniques performed in 51 patients are discussed. Sector-shaped iris segments required longer surgery because of the complexity of intracameral sutures and carried risks for knots to loosen and sutures to cut through residual iris tissue. The combined implantation of an iris and IOL proved complex and lengthy but solved lens and iris abnormalities in 1 procedure and provided long-lasting stable conditions. The procedures that implanted a complete iris in pseudophakic eyes were shorter and required smaller incisions, a sutureless approach, and injector-assisted implantation.